Experimental Characterization of Wearable Antennas and Circuits for RF Energy Harvesting in WBANs - Saraiva, Henrique Morais (2014)
Field trials have been performed in Covilhã to identify the spectrum opportunities for radio frequency (RF) energy harvesting through power density measurements from 350 MHz to 3 GHz. Based on the identification of the most promising opportunities, a dual-band printed antenna was conceived, operating at GSM bands (900/1800), with gains of 1.8 and 2.06 dBi, and efficiency varying from 77.6 to 82%, for the highest and lowest operating frequency bands, respectively. In this paper, guidelines for the design of RF energy harvesting circuits and choice of textile materials for a wearable antenna are briefly discussed. Besides, we address the development and experimental characterization of three different prototypes of a five-stage Dickson voltage multiplier (with and without impedance matching circuit) responsible for RF energy harvesting. All the three prototypes (1, 2 and 3) can power supply the sensor node for RF received powers of 2 dBm, -3 dBm and -4 dBm, and conversion efficiencies of 6, 18 and 20%, respectively.